Gestão da eficiência energética em salas de aula de instituições federais de ensino - Ascari, Vagner Miguel (2020)
Energy efficiency is a very important issue and the expenses derived from it represent a considerable part of the fixed costs of the organizations, being important and current the practice of actions aimed at energy efficiency. In view of the above, the objective of analysis of the challenges and ways to implement projects in efficiency in the classroom environments of Federal Education Institutions, having as object of study the Federal University of Mato Grosso - UFMT. To meet the proposed objective for an investigation, a case study was chosen, using applied research, with a qualitative approach. Based on this research, a proposal is made for the implementation of software managed by an application for the control and automation of lamps and air conditioning devices, Start_IoT, based on the concept of Internet of Things (IoT) - devices and equipment of the physical world integrated via internet. The results, sought to search for them in classrooms, demonstrated that the waste of electric energy and improper use of the environment is necessary, and the research brought the benefits of an automatic intervention in detriment to the manual control of the equipment activation (with the perceptions and opinions with users and experts). For an analysis of the research on the topic, a technological survey was carried out and a survey is concluded with the presentation of a protocol for diagnosing energy consumption in classrooms. In order to promote practical results, the research resulted in three technical-technological products: a technological prospecting article on the topic, the registration of the Start_IoT software and a conclusive technical report.